Multiaxial Fatigue 1985
DOI: 10.1520/stp36221s
|View full text |Cite
|
Sign up to set email alerts
|

Mode I Fatigue Crack Growth Under Biaxial Stress at Room and Elevated Temperature

Abstract: Fatigue crack growth rates have been measured in different biaxial stress fields for a variety of stress ranges at two temperatures. It is shown that a negative T-stress accelerates the crack propagation, the increase in growth rate being greater for high stresses. Different methods of determining plastic zone size are compared, and a crack growth correlation with crack-tip plasticity is proposed for remote loads not greater than the yield stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
6

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 14 publications
3
21
0
6
Order By: Relevance
“…He investigated various biaxiality ratios. McClung et al later [1] revisited these investigations and reported the general trends found for R = 0 and R = À1 to be consistent with experimental data, McClung and Sehitoglu [24], Brown and Miller [42], Hoshide et al [47].…”
Section: Multiaxial Loadingmentioning
confidence: 52%
See 1 more Smart Citation
“…He investigated various biaxiality ratios. McClung et al later [1] revisited these investigations and reported the general trends found for R = 0 and R = À1 to be consistent with experimental data, McClung and Sehitoglu [24], Brown and Miller [42], Hoshide et al [47].…”
Section: Multiaxial Loadingmentioning
confidence: 52%
“…Research began with investigations of loading cases with fixed principal axes: Biaxial and proportional loading [42][43][44][45][46][47][48][49][50][51][52][53][54][55]. The common feature of most of these modelling approaches is that the driving force parameters are composed of two factors: a function of the crack length and the hardening exponent together with the ranges of the far-field loading.…”
Section: Multiaxial Loadingmentioning
confidence: 99%
“…The in-plane constraint [96][97] can be most conveniently studied by considering a mode I crack and varying the magnitude and direction of the applied stress level parallel to the crack, Sx (Sy = Constant, Sz = 0). The cruciform geometry used to study this phenomenon is shown in Figure 12(a).…”
Section: Out-of-plane and In-plane Constraintmentioning
confidence: 99%
“…This creates a reversed (or cyclic) plastic zone ahead of the crack tip within the monotonic plastic zone [9,10]. Further works relating the fatigue crack growth rate to plastic zones relied on using this ideology of a reversed plastic zone [11,12]. It was determined that a larger reversed plastic zone size would cause an increase in the fatigue crack growth rate.…”
Section: Introductionmentioning
confidence: 99%